Simultaneous determination of minoxidil and minoxidil sulfate by high-performance liquid chromatography with UV-detection and its applications - Mio Ichida; Chiharu Fujita; Rena Sumie; Ryotaro Miyano; Hajime Inoue (Elsevier, 2020)
Aims: Minoxidil is a hair growth drug for treating androgenetic alopecia. Although minoxidil is generally administered as a topical formulation, this prodrug must be converted to its active form (minoxidil sulfate) by sulfotransferase in hair follicle tissue. Therefore, its effect may be affected by the sulfureting of minoxidil and de-sulfureting of minoxidil sulfate in hair follicles. To investigate the biotransformation of minoxidil sulfate to minoxidil in hair follicle component cells, a method for simultaneous determination of minoxidil and minoxidil sulfate by high-performance liquid chromatography with UV-detection was established. Main methods: Minoxidil and minoxidil sulfate were separated by a reversed-phase chromatography. Minoxidil sulfate was incubated with human hair follicle keratinocyte- and dermal papilla cell-derived arylsulfatases as well as snail-derived sulfatase. The enzyme mixture was applied on HPLC system directly. Key findings: Minoxidil and minoxidil sulfate were separated simultaneously. The limit of detection of minoxidil and minoxidil sulfate was 25 and 100 pg inj−1, respectively. Snail-derived sulfatase as well as human hair follicle keratinocyte- and dermal papilla cell-derived arylsulfatases hydrolyzed minoxidil sulfate to minoxidil. Arylsulfatase in hair follicle metabolized the active form of minoxidil to the inactive form. Inactivation of active minoxidil (sulfate) was inhibited by the natural substrate of arylsulfatase A, ascorbate-2-sulfate. Significance: Arylsulfatase inhibitors may sustain the effect of minoxidil sulfate in AGA therapy. The developed technique was effective for studies of minoxidil metabolism and bioavailability.